Analisia Kinerja Rumah Sakit Umum Daerah Dr. H. Abdul Moeloek Provinsi Lampung Tahun 2011- 2013 Berdasarkan Balanced Scorecard - Muliati, Laisa (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2017)
RSUDAM as public sector organizations BLUD status, health services should be held responsible, effective and efficient. It required comprehensive tools as a form of accountability to the community or the owner. Balanced scorecard by many nonprofits regarded as a comprehensive measuring tool. Namely the customer perspective, financial, internal business process perspective and the perspective of growth and learn. to analyze the performance of RSUDAM years 2011-2013 based balanced scorecard.The data analysis univariate analysis (descriptive). Data processing with methods of qualitative and quantitative studies of secondary data research activities in 2011-2013 show that: 1) The performance of the customer's perspective: Patient satisfaction: in 2012 amounted to 73.75% satisfied, in 2013 amounted to 75.88% satisfied, share broad market, retention and customer acquisition shows an increasing trend 2) Performance on the financial perspective: income on health services has increased, with declining growth 3) Performance on the internal business perspective: shows the process of quality improvement 4) Performance of growth and learning:the program directed to increase competence, motivation and discipline employees not maximized results in improved performance in real terms. Balanced Scorecard framework as alternative which able to be used on performance assesment of RSUDAM because more comprehensiv than performance in measurement is RSUDAM now